2018
DOI: 10.3390/met8060398
|View full text |Cite
|
Sign up to set email alerts
|

The Aqueous Electrochemical Response of TiC–Stainless Steel Cermets

Abstract: A family of TiC-stainless steel ceramic-metal composites, or cermets, has been developed in the present study, using steel grades of 304 L, 316 L, or 410 L as the binder phase. Melt infiltration was used to prepare the cermets, with the steel binder contents varying between 10-30 vol. %. The corrosion behaviour was evaluated using a range of electrochemical techniques in an aqueous solution containing 3.5 wt. % NaCl. The test methods included potentiodynamic, cyclic, and potentiostatic polarisation. The corrod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Similarly, reducing the amount of Co binder increases the corrosion resistance [2], with selective leaching of Co noted in this study. In a similar vein, it was also shown for TiC-stainless steel cermets (grades 304L, 316L, and 410L) that corrosion resistance decreased with increasing steel binder content, while the steel composition also had a significant effect [5]; at the lowest binder contents (i.e., 10 vol.% steel), the corrosion resistance was comparable to the steel on its own, while the cermet had a roughly three-orders of magnitude lower wear rate. In comparing WC-WB-Co and WC-FeCrAl coatings, it was shown that the latter exhibited slightly improved corrosion resistance [3], although the two systems were broadly comparable.…”
Section: Contributionsmentioning
confidence: 55%
See 2 more Smart Citations
“…Similarly, reducing the amount of Co binder increases the corrosion resistance [2], with selective leaching of Co noted in this study. In a similar vein, it was also shown for TiC-stainless steel cermets (grades 304L, 316L, and 410L) that corrosion resistance decreased with increasing steel binder content, while the steel composition also had a significant effect [5]; at the lowest binder contents (i.e., 10 vol.% steel), the corrosion resistance was comparable to the steel on its own, while the cermet had a roughly three-orders of magnitude lower wear rate. In comparing WC-WB-Co and WC-FeCrAl coatings, it was shown that the latter exhibited slightly improved corrosion resistance [3], although the two systems were broadly comparable.…”
Section: Contributionsmentioning
confidence: 55%
“…The current special issue, with a focus on cermets and hardmetals, brings together seven scientific research papers [1][2][3][4][5][6][7] that investigate various aspects of these materials. The papers are broadly divided between WC-based hardmetal systems [1][2][3][4], lower density carbides including TiC [5] and NbC [6], and mixed oxide-carbide systems [7]. In two examples, the hardmetal is present as a thin coating on Cr-Ni-Mo based steel substrates [3,4].…”
Section: Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides that, the extension of the pseudo-passive region for the Al 0.9 CoCuCrFe alloy was almost the same (96 mV vs 100 mV for the Al 0.5 CoCuCrFe alloy). This region can be related to the formation of porous or poor protective oxide [ 24 ]. It is important to clarify that the corrosion tests were carried out just after the sanding of the surface of the sample; therefore, there was no time to form an appreciable oxide layer.…”
Section: Resultsmentioning
confidence: 99%